Measuring the impact of cataract services in the community - Sarah Polack; Hannah Kuper (Community Eye Health Journal, 2014)
In many low-income countries, a substantial number of people remain needlessly visually impaired or blind from cataract as a result of not accessing surgical services.1 In this article, we will discuss how Rapid Assessment of Avoidable Blindness (RAAB) surveys can play a role in improving cataract services, and the impact that sight-restoring cataract surgery can have on people’s lives.